Role of hypoxic exosomes and the mechanisms of exosome release in the CNS under hypoxic conditions - Yang, Rong; Li, Zheng; Xu, Jing; Luo, Juan; Qu, Zhichuang; Chen, Xin; Yu, Sixun; Shu, Haifeng (Frontiers in Neurology, 2023)
Hypoxia is characterized by low oxygen levels in the body or environment, resulting in various physiological and patholog-ical changes. The brain, which has the highest oxygen con-sumption of any organ, is particularly susceptible to hypoxic injury. Exposure to low-pressure hypoxic environments can cause irreversible brain damage. Hypoxia can occur in healthy individuals at high altitudes or in pathological condi-tions such as trauma, stroke, inflammation, and autoimmune and neurodegenerative diseases, leading to severe brain damage and impairments in cognitive, learning, and memory functions. Exosomes may play a role in the mechanisms of hypoxic injury and adaptation and are a current focus of re-search. Investigating changes in exosomes in the central nervous system under hypoxic conditions may aid in pre-venting secondary damage caused by hypoxia. This paper provides a brief overview of central nervous system injury resulting from hypoxia, with particular emphasis on high-altitude hypoxic injury. This review aimed to investigate the role and mechanism of exosomes in craniocerebral injury caused by hypoxia.